Crystallography in Sand, Stendhal, Pictet, and Baudelaire. (July 2013) - M, M
Abstract : This article examines engagements between crystallography and literary texts in nineteenth-century France. It argues that the newly reached understanding of crystallization at the beginning of the century provided writers with new concepts and images for thinking through issues concerning the imagination and ways of understanding reality. Focusing on works by Stendhal, Adolphe Pictet, Charles Baudelaire, and George Sand, the article reveals how these writers employ the image of the crystal and the logic of crystal formation to explore notions of power, transformation, and the attraction or union of different approaches to reality.